2007
DOI: 10.1042/bj20061291
|View full text |Cite
|
Sign up to set email alerts
|

TLXI, a novel type of xylanase inhibitor from wheat (Triticum aestivum) belonging to the thaumatin family

Abstract: Wheat (Triticum aestivum) contains a previously unknown type of xylanase (EC 3.2.1.8) inhibitor, which is described in the present paper for the first time. Based on its >60% similarity to TLPs (thaumatin-like proteins) and the fact that it contains the Prosite PS00316 thaumatin family signature, it is referred to as TLXI (thaumatin-like xylanase inhibitor). TLXI is a basic (pI> or =9.3 in isoelectric focusing) protein with a molecular mass of approx. 18-kDa (determined by SDS/PAGE) and it occurs in wheat with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
123
1
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 142 publications
(135 citation statements)
references
References 51 publications
7
123
1
3
Order By: Relevance
“…XIP-and TLXI-type XIs are basic, monomeric proteins with a molecular mass of ~30 and ~18 kDa, respectively [16,17]. Multiple putative TAXI-[18, 21, 22] and XIP-type [19,23] as well as one TLXI-type gene(s) [17] have been identified in wheat and some have been confirmed. For the three types of XIs, the existence of various forms as well as differences in their spatio-temporal location, due to distinct regulatory control mechanisms, have been suggested.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…XIP-and TLXI-type XIs are basic, monomeric proteins with a molecular mass of ~30 and ~18 kDa, respectively [16,17]. Multiple putative TAXI-[18, 21, 22] and XIP-type [19,23] as well as one TLXI-type gene(s) [17] have been identified in wheat and some have been confirmed. For the three types of XIs, the existence of various forms as well as differences in their spatio-temporal location, due to distinct regulatory control mechanisms, have been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…To allow detection of eventually truncated N-and C-termini, the custom database was subsequently N-and C-terminally 'ragged' using DBToolkit prepared by spotting 1 µl of a mixture of sample and matrix (7 mg/ml CHCA in 50% ACN containing 0.1% TFA) on a stainless steel (192-well) MALDI target plate and allowed to air-dry at RT. Prior to MALDI-MS analysis, the instrument was externally calibrated with a mixture of Angiotensin I, Glu-fibrino-peptide B, ACTH (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), and ACTH (18-39). For MS/MS experiments, the instrument was externally calibrated with fragments of Glu-fibrino-peptide.…”
Section: Protein Identification By Tandem Mass Spectrometric Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Purified TLPs from several plant species have in vitro anti-fungal activity. Several antifungal modes of action have been described such as membrane permeabilization (Vigers et al 1991), β-glucan binding and degradation (Sakamoto et al 2006), inhibition of enzymes such as xylanases (Fierens et al 2007), α-amylase, or trypsin (Schimoler-O'Rourke et al 2001, as well as an apoptosisinducing mechanism reported in yeast (Narasimhan et al 2005). A PR5 protein from Arabidopsis thaliana ATLP3, showed considerable antifungal activity against pathogenic fungi such as Verticillium alboatrum, V. dahliae and Fusarium oxysporum (Hu and Ready 1997).…”
Section: Introductionmentioning
confidence: 99%